DISKURSUS MUNÄ€SABAH: Problem TafsÄ«r al-Qurâ€™Än bi â€™l-Qurâ€™Än - Affani, Syukron (Jurnal THEOLOGIA, 2017)
Abstract: MunÄsabah al-Qurâ€™Än is a part of â€˜UlÅ«m al-Qurâ€™Än which presents pros and contrast. The pros ulama makes munÄsabah as a method to reveal enigma system of Quran verses and chapter. The structure of the Quranâ€™s verses and chapters seems to leap and are not connected each other. But for ulama who are contra to munÄsabah, this success considered as a subjective product which did not put munÄsabah tafsÄ«r as á¸¥ujja tafsÄ«r automatically. As a questionious Quranâ€™s knowlÂedge, munÄsabah has become a tafsÄ«r method al-Qurâ€™Än bi â€™l-Qurâ€™Än (textual relations in the Quran) which is in the highest position in the hierarchy of tafsÄ«r bi â€™l-maâ€™thÅ«r with the highest á¸¥ujja (a binding proof) status. Quranic exegesis is called maâ€™thÅ«r if it is based upon the traditions of the Prophet, his Companions, and the immediate Successors of the Companions. The active subject as athÄ«r in the tafsÄ«r bi â€™l-maâ€™thÅ«r is the prophet in the tafsÄ«r al-Qurâ€™Än bi â€™l-á¸¤adÄ«th; ComÂpanions in the tafsÄ«r al-Qurâ€™Än bi aqwÄl al-á¹£ahÄba; and tÄbiâ€™Ä«n â€˜the immediate Successors of the Companionsâ€™ in the tafsÄ«r al-Qurâ€™Än bi aqwÄl al-tÄbiâ€™Ä«n which the explanation or behavior is athar which is made as the base (maâ€™thÅ«r) of the interpretation. But what about the exegesis of al-Qurâ€™Än bi â€™l-Qurâ€™Än: is Allah as the active subject or a Quranic naá¹£? If Allah, of course, he delivers it through the prophet and it belongs to tafsÄ«r al-Qurâ€™Än bi â€™l-á¸¤adÄ«th category. If Allah analogically through al-Qurâ€™Än naá¹£ truly, so does this al-Qurâ€™Än naá¹£ automatically become the base of another al-Qurâ€™Än naá¹£ or it still needs the help of an interpreter? This question becomes an epistemological problem of tafsÄ«r al-Qurâ€™Än bi â€™l-Qurâ€™Än through the helping knowledge, it is munÄÂsabah al-Qur'an. The formulation of the problem in this paper, firstly, how the method of munÄsabah operates in the al-Qurâ€™Än bi â€™l-Qurâ€™Än interpretation. Secondly, what is the impact of the munÄsabah method works on the status of the al-Qurâ€™Än bi â€™l-Qurâ€™Än interpretation. The result, firstly, the method of munÄsabah used to explain one verse against another, is ijtihÄdy; and secondly, it affects to the maâ€™thÅ«r and á¸¥ujja status of the al-Qurâ€™Än bi â€™l-Qurâ€™Än interpretation which has been getting the top spot in the hierarchy of interÂpretation bi â€™l-ma'thÅ«r so that necessary reformulation Quranic interÂpretation bi â€™l-ma'thÅ«r.Abstrak: MunÄsabah al-Qurâ€™Än termasuk bagian dari â€˜UlÅ«m al-Qurâ€™Än yang mengundang pro dan kontra. Ulama yang pro menjadikan munÄsabah sebagai metode untuk mengungkap enigma sistematika ayat dan surat al-Qurâ€™Än. Sepintas susunan ayat dan surat melompat-lompat dan dirasakan tidak saling terhubung. Tetapi bagi ulama yang kontra munÄsabah, keberhasilan tersebut merupakan produk subjektif yang tidak serta merta menempatkan tafsir-tafsir munÄsabah sebagai tafsir á¸¥ujjah. Sebagai ilmu al-Qurâ€™Än yang dipersoalkan, munÄsabah telah menjadi metode tafsÄ«r al-Qurâ€™Än bi â€™l-Qurâ€™Än yang secara hirarkis menempati posisi teratas tafsÄ«r bi â€™l-maâ€™thÅ«r dengan status kehujjahan tertinggi. Suatu penafsiran disebut maâ€™thÅ«r bila disandarkan kepada al-Qur'an sendiri, hadits atau sunnah Nabi, qaul Sahabat, dan Tabiâ€™in. Subjek aktif sebagai athÄ«r pada tafsÄ«r bi â€™l-maâ€™thÅ«r adalah Nabi pada tafsÄ«r al-Qurâ€™Än bi â€™l-á¸¤adÄ«th; Sahabat pada tafsÄ«r al-Qurâ€™Än bi aqwÄl al-á¹£ahÄbah; dan tÄbiâ€™Ä«n pada tafsir al-Qurâ€™Än bi aqwÄl al-tabiâ€™Ä«n yang keterangan atau tindak perilakunya adalah atsar yang dijadikan dasar (maâ€™thÅ«r) penafsiran. Tetapi bagaimana dengan tafsÄ«r al-Qurâ€™Än bi â€™l-Qur'Än: apakah Allah sebagai subjek aktifnya atau naá¹£ al-Qur'an? Kalau Allah, tentu melalui Nabi dan itu berarti masuk kategori tafsÄ«r al-Qurâ€™Än bi â€™l-á¸¥adÄ«th. Kalau Allah (secara majÄzÄ«) melalui naá¹£ al-Qurâ€™an secara haqÄ«qÄ«, maka apakah naá¹£ al-Qurâ€™an ini menjadi dasar penafsiran naá¹£ al-Qurâ€™an yang lain dengan sendirinya atau dengan bantuan penafsir? Pertanyaan ini menjadi problem episteÂmologis tafsÄ«r al-Qurâ€™Än bi â€™l-Qurâ€™Än melalui ilmu bantuÂnya yaitu munÄsabah al-Qur'an. Rumusan masalah dalam tulisan ini pertama, bagaimanakah metode munÄsabah beroperasi dalam tafsir al-Qur'an dengan al-Qur'an. Kedua, apa dampak cara kerja metode munÄsabah terhadap status tafsÄ«r al-Qurâ€™Än bi â€™l-Qurâ€™Än. Hasilnya, pertama, metode munÄsabah yang dimanfaatkan untuk menjelaskan satu ayat terhadap ayat yang lain, bersifat ijtihÄdÄ«; dan kedua, karena itu berpengaruh terhadap status kemaâ€™tsuran dan kehujjahan tafsÄ«r al-Qurâ€™Än bi â€™l-Qurâ€™Än yang selama ini mendapatkan tempat teratas dalam hirarki tafsir bi â€™l-maâ€™thÅ«r sehingga diperlukan reformulasi tafsir bi â€™l-maâ€™thÅ«r.